Government spending and voting behaviour: evidence from subsidized graduation trips - Arcidiacono, Malena (2023)
Ruling parties around the world oftentimes make active use of public funds during electoral campaigns to sway votes in their favor, with widely varying degrees of success. I study the effectiveness of a one-time targeted cash transfer on the voting behavior of young people. I focus on the Province of Buenos Aires (PBA), Argentina, which is well-suited to examine these issues. First, the spending program was announced between primary and general elections. Second, the percentage of beneficiaries varies across voting booths. Third, between the two elections, the ruling party "Frente de Todos" increased the vote share substantially. I leverage province- and group-specific variation along with individual and voting-booth level administrative data and find that the youth increased their support to the incumbent government following the trip subsidy.